Perilaku Informasi Mahasiswa dan Hoaks di Media Sosial - Nurrahmi, Febri; Syam, Hamdani M. (Communicatus: Jurnal Ilmu komunikasi, 2020)
The rise of hoaxes circulating on social media makes students as active social media users vulnerable to distribute hoaxes. The study used the model of information behavior by Wilson (1996) to examine information behaviors of university students in combating hoaxes on social media. Using a qualitative method, data collection was conducted through focus groups discussions with 14 students of Syiah Kuala University. The results showed that the information behaviors performed by the university students were not adequate to combat hoaxes. The critical attitude by not easily trusting information on social media was not accompanied by sufficient will and abilities to verify information they received from social media. Information dissemination behavior without verification was also found in this study. The results of this study also indicated that passive attention and search were the most dominant information behaviors among students. The results also showed that low self-efficacy encourage students to be reluctant and difficult to conduct information searches for verification. This study suggested that the model of information behaviour by Wilson (1996) was relevant to discuss studentsâ€™ information behavior to combat hoaxes on social media. These findings are important to develop a social media literacy model for university students to fight against hoaxes on social media. Â Maraknya hoaks yang beredar di media sosial menjadikan mahasiswa sebagai pengguna media sosial aktif rentan menjadi penyebar hoaks. Penelitian menggunakan model perilaku informasi oleh Wilson (1996) untuk melihat perilaku informasi mahasiswa dalam menghadapi hoaks di media sosial. Dengan menggunakan metode kualitatif, pengumpulan data dilakukan dengan focus groups discussion terhadap 14 orang mahasiswa Universitas Syiah Kuala. Hasil penelitian menunjukkan perilaku informasi mahasiswa dalam menghadapi hoaks belum mumpuni. Sikap kritis dengan tidak mudah mempercayai informasi di media sosial, ternyata tidak disertai kemauan dan kemampuan verifikasi informasi yang memadai. Perilaku penyebaran informasi tanpa verifikasi juga masih ditemukan. Hasil studi ini juga mengindikasikan bahwa perilaku perhatian dan pencarian pasif adalah perilaku yang paling dominan di kalangan mahasiswa. Hasil studi menunjukkan bahwa self-efficacy yang rendah menyebabkan mahasiswa enggan dan sulit melakukan pencarian informasi untuk verifikasi. Studi ini menunjukkan bahwa model perilaku informasi oleh Wilson (1996) relevan untuk membahas perilaku informasi mahasiswa dalam menghadapi hoaks di media sosial. Hasil studi ini penting untuk mengembangkan model literasi media sosial di kalangan mahasiswa untuk menangkal hoaks.